1999
DOI: 10.1128/mcb.19.1.296
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase Binds with Transcription Enhancer Factor 1 to MCAT1 Elements To Regulate Muscle-Specific Transcription

Abstract: Multicellular organisms express many genes in a cell-typespecific fashion. The mechanisms governing cell-specific gene expression are becoming increasingly understood at two levels. First, there are numerous examples in which the binding of nuclear transcription factors to cis elements within gene regulatory regions has been shown to govern cell-specific activation of gene transcription. A second level of regulation has been proposed to be mediated by the remodeling of chromatin organization both globally and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
176
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(181 citation statements)
references
References 58 publications
(73 reference statements)
5
176
0
Order By: Relevance
“…PARP1, a prototype member of the large PARP family, has been shown to interact with TEF1 to form a complex on M-CAT binding sites of the cardiac troponinT and MHC genes, leading to their muscle-specific gene regulation [136,137]. We as well as others have previously reported that PARP1 is activated during both physiologic and pathologic hypertrophy, and that its levels are further elevated in failing hearts [107,135,138].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 79%
See 1 more Smart Citation
“…PARP1, a prototype member of the large PARP family, has been shown to interact with TEF1 to form a complex on M-CAT binding sites of the cardiac troponinT and MHC genes, leading to their muscle-specific gene regulation [136,137]. We as well as others have previously reported that PARP1 is activated during both physiologic and pathologic hypertrophy, and that its levels are further elevated in failing hearts [107,135,138].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 79%
“…In regard to what is known about the intracellular stimuli of PARP1, at least two signaling pathways, an increased intracellular Ca 2+ level and the activation of ERK1/2, have been found to activate PARP1 during hypertrophy [140,141]. By analysis of PARP-inhibitors, it was found that PARP activates the TEF1-mediated gene transcription from the M-CAT sites [136]. In contrast, in a transient assay, over expression of PARP1 was found to repress the transcription of genes containing the M-CAT sites, again suggesting that PARP1 has a dual role in gene expression, activation followed by repression, depending upon the degree of PARP activation [107].…”
Section: Chromatin Modifying Enzymesmentioning
confidence: 99%
“…repair proteins and the biological e ects observed are solely due to the absence of poly(ADP-ribosyl)ation. By contrast, knocking out PARP either by homologous recombination or by expressing PARP antisense RNA interferes with any function of PARP protein, including poly(ADP-ribosyl)ation, binding to DNA strand breaks and, as shown recently, in¯uences on transcription (Oei et al, 1998;Butler and Ordahl, 1999). Thus it is conceivable that, if PARP has several functions, a complete loss of all of these functions due to gene targeting or antisense technology can result in a di erent phenotype than loss of only one function such as catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…The role of PARP in the regulation of transcription of the E2F-1 and pol a genes may be indirect, given that PARP has also been shown to enhance activator-dependent transcription by interacting with RNA polymerase II-associated factors (Meisterernst et al, 1997). PARP also binds transcription enhancer factor 1 (TEF1) to enhance muscle-speci®c gene transcription (Butler and Ordahl, 1999) as well as the transcription factor AP-2 to coactivate AP-2-mediated transcription (Kannan et al, 1999). The basal transcription factor TFIIF and TEF-1 are both highly speci®c substrates for poly(ADPribosyl)ation (Butler and Ordahl, 1999;Rawling and Alvarez-Gonzalez, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…PARP also binds transcription enhancer factor 1 (TEF1) to enhance muscle-speci®c gene transcription (Butler and Ordahl, 1999) as well as the transcription factor AP-2 to coactivate AP-2-mediated transcription (Kannan et al, 1999). The basal transcription factor TFIIF and TEF-1 are both highly speci®c substrates for poly(ADPribosyl)ation (Butler and Ordahl, 1999;Rawling and Alvarez-Gonzalez, 1997). Whether PARP modulates E2F-1-mediated transcription by binding to E2F-1 remains to be clari®ed.…”
Section: Discussionmentioning
confidence: 99%